The application of ethanol-extracted Gloriosa superba for metaphase chromosome preparation in mosquitos - Choochote W. (2014)
The application of ethanol-extracted Gloriosa superba for metaphase chromosome preparation in adult and 4th larva Aedes aegypti revealed that 0.5-8% ethanol-extracted Gl. superba solution could be used instead of 1% colchicine in Hanks' balanced salt solution. For adult mosquitos, the metaphase rates and average number of metaphase chromosomes per positive mosquito after intrathoracic inoculation with 1-2% ethanol-extracted Gl. superba solution were 100% and 11.8 (2-16) -12.6 (3-28) in females, and 80-90% and 16.5 (1-52) - 29.89 (1-72) in males, whereas the inoculation with 1% colchicine solution yielded 80% and 50% metaphase rates, and 18.25 (1-40) and 16.5 (2-53) average number of metaphase chromosomes per positive mosquito in females and males, respectively. For 4th stage larvae, the metaphase rates and average number of metaphase chromosomes per positive mosquito after incubation with 0.5-8% ethanol-extracted Gl. superba solution were 90-100% and 14.42 (1-65) - 64 (19-137), while incubation with 1% colchicine solution yield 100% metaphase rate and 10.9 (7-15) average number of metaphase chromosomes per positive mosquito.